2022
DOI: 10.3390/ijerph192315609
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Resistance in Patients with Peri-Implantitis: A Systematic Scoping Review

Abstract: The implementation of adjunctive antibiotics has been recommended for the therapy of peri-implantitis (PI). In this review, antibiotic resistance patterns in PI patients were assessed. A systematic scoping review of observational studies and trials was established in conjunction with the PRISMA extension for scoping reviews. The SCOPUS, PubMed/MEDLINE, EMBASE, SCIELO, Web of Science, and LILACS databases were reviewed along with the gray literature. The primary electronic examination produced 139 investigation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 52 publications
2
12
0
1
Order By: Relevance
“… 2 , 28 A study on antibiotic resistance in peri-implantitis revealed high resistance of periodontal pathogens, such as P. gingivalis, Aggregatibacter actinomycetemcomitans, T. forsythia , and Prevotella intermedia , to tetracycline, clindamycin, metronidazole, erythromycin, and azithromycin. 29 In the present case of lung abscess following dental implantation, the main pathogen identified was T. forsythia , along with mixed infection of P. gingivalis, Actinomyces , and other bacteria. The pathogen profile was similar to that commonly observed in periodontal diseases and peri-implantitis.…”
Section: Discussionmentioning
confidence: 63%
“… 2 , 28 A study on antibiotic resistance in peri-implantitis revealed high resistance of periodontal pathogens, such as P. gingivalis, Aggregatibacter actinomycetemcomitans, T. forsythia , and Prevotella intermedia , to tetracycline, clindamycin, metronidazole, erythromycin, and azithromycin. 29 In the present case of lung abscess following dental implantation, the main pathogen identified was T. forsythia , along with mixed infection of P. gingivalis, Actinomyces , and other bacteria. The pathogen profile was similar to that commonly observed in periodontal diseases and peri-implantitis.…”
Section: Discussionmentioning
confidence: 63%
“…It is important to note that the heterogeneity of the randomized clinical trials examined in this systematic review precluded a more thorough study. Some recent systematic reviews [ 47 , 48 ] have revealed the exact same issues. The diverse behavior of systematic reviews, in terms of the clinical trials included, justifies the standardization of clinical techniques so that comparisons between clinical trials may be made without prejudice.…”
Section: Discussionmentioning
confidence: 87%
“…Bacteria colonise various implant surfaces, such as dental implants, catheters, and orthopaedic implants [53]. Furthermore, antibiotic resistance directly contributes to implant failures due to the formation of biofilms on these surfaces [54,55]. In response to this concern, numerous studies have been undertaken to develop physical and chemical methods aimed at reducing bacterial colonisation [56,57].…”
Section: Polymers Used In Biomedical Applicationsmentioning
confidence: 99%